Insuficiencia de la comprensión lectora y el rendimiento académico de los estudiantes de Educación Básica Nivel Superior de la Unidad Educativa Intercultural Bilingüe “Cochapamba”, Diseño de un Manual de Estrategias Metodológicas. - Yánez Ávila, Nelly Margoth. (2019)
The present investigation started from the study of reading comprehension and academic performance of upper level basic education students, and the design of a manual of methodological strategies, which lead to the development of reading skills. The main objective of this study was to determine the strategic skills that allow the development of reading comprehension in the academic performance of students of higher basic general education of the Bilingual Intercultural Educational Unit "Cochapamba", and propose the design of a manual with the purpose of to improve academic performance and reading comprehension in students. To achieve this objective, a theoretical analysis of reading comprehension skills and strategies, a determining factor of student performance in the educational institution, was carried out. Subsequently, data collection was carried out in the institution, to determine the application of various activities that strengthen reading comprehension and raise the level of academic performance of the students. The lack of didactic resources for teachers and students in the practice of the reading process was detected. However, the predisposition of teachers and students was observed to get involved in the reading-writing process, which is determined to be pertinent to plan, the proposal with the design of a Manual of methodological strategies, using workshops that lead to the development of reading skills at the inferential, analogical and evaluative levels of reading.